2021
DOI: 10.2196/24618
|View full text |Cite
|
Sign up to set email alerts
|

Development of Social Support Networks by Patients With Depression Through Online Health Communities: Social Network Analysis

Abstract: Background In recent years, people with mental health problems are increasingly using online social networks to receive social support. For example, in online depression communities, patients can share their experiences, exchange valuable information, and receive emotional support to help them cope with their disease. Therefore, it is critical to understand how patients with depression develop online social support networks to exchange informational and emotional support. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…Third, as a significant finding of capturing users' emotional changes on the population level, the “rebound effect” showed that posting a highly negative microblog could relieve the user's negative emotions in our analysis. Social media supplies troubled people with a free space where they may share worries and other expressions of a bad mood, which helps relieve negative emotions stirred by disasters and heighten well-being ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, as a significant finding of capturing users' emotional changes on the population level, the “rebound effect” showed that posting a highly negative microblog could relieve the user's negative emotions in our analysis. Social media supplies troubled people with a free space where they may share worries and other expressions of a bad mood, which helps relieve negative emotions stirred by disasters and heighten well-being ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…When verifying the moderating effect of chronic diseases, the sample was differentiated only in terms of an indicator of the presence of a chronic disease, which was a quite simple measure. Future studies can consider different types of disease and employ richer measures to verify the moderating effect of disease types on patients’ behavioral patterns, such as by reference to mental health ( Lu et al, 2021 ) or albinism ( Bi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, friendship among patients can be promoted and better interpersonal relationships can be constructed when patients post in OHCs, communicate and share EHRs candidly with doctors and patients online. Previous studies have shown that patients with mental health issues tend to utilize online depression communities to share experiences and exchange valuable information and emotional support to cope with their own diseases ( Lu et al, 2021 ). Moreover, another study verified that the information provided via OHCs is moderately understandable and reliable, which can encourage and motivate patients to participate in such communities to improve their health ( Kavosi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, emotional support is defined as psychological support, such as sympathy, care or understanding, which can comfort users psychologically and help resolve problems indirectly. Hence, social support, in addition to enriching information sources, also warms individual’s heart ( Lu et al, 2021 ). The favorable experience can enhance users’ willingness to seek social interaction with other users, while support providers can also obtain the sense of identity from interaction of the kind ( Atanasova and Petric, 2019 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%